2011
DOI: 10.1007/s00595-011-4509-z
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemoradiotherapy using cisplatin plus s-1, an oral fluoropyrimidine, followed by surgery for selected patients with stage III non-small cell lung cancer: A single-center feasibility study

Abstract: Induction treatment using S-1 plus cisplatin and concurrent radiotherapy and surgical resection for selected patients with stage III NSCLC is a feasible and promising new treatment modality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Sudo et al [25] reported that CCRT with S-1 showed a promising antitumor effect, with a response rate of 41% and an MST of 16.8 months with acceptable toxicity in patients with locally advanced pancreatic cancer. CCRT with S-1 plus cisplatin for locally advanced non-small cell lung cancer has shown promising efficacy outcomes of 86.4-87.5% combined with good survival rates (24.4-33.1 months) and mild toxicity [26,27]. Likewise, CCRT with S-1 plus cisplatin for head and neck cancer is expected [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sudo et al [25] reported that CCRT with S-1 showed a promising antitumor effect, with a response rate of 41% and an MST of 16.8 months with acceptable toxicity in patients with locally advanced pancreatic cancer. CCRT with S-1 plus cisplatin for locally advanced non-small cell lung cancer has shown promising efficacy outcomes of 86.4-87.5% combined with good survival rates (24.4-33.1 months) and mild toxicity [26,27]. Likewise, CCRT with S-1 plus cisplatin for head and neck cancer is expected [28].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, clinical studies of CCRT with S-1 for locally advanced pancreatic cancer [25] and CRT with S-1 plus cisplatin for non-small cell lung cancer [26,27], and head and neck cancer [28] have been attempted. Sudo et al [25] reported that CCRT with S-1 showed a promising antitumor effect, with a response rate of 41% and an MST of 16.8 months with acceptable toxicity in patients with locally advanced pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with marginally resectable stage III NSCLC, a small phase II trial has also reported that the safety and efficacy of induction treatment using S-1 plus CDDP and concurrent TRT and surgical resection was a feasible and promising new treatment modality [Maruyama et al 2011].…”
Section: Chemoradiotherapy Containing S-1 For Locally Advanced Nsclcmentioning
confidence: 99%